Development of strategic management of a corporation through the implementation of scenario analysis - V. Makedon; V. Myachin; N. Kuriacha; Yu. Chaika; D. Koptilyi (Науковий вісник Мукачівського державного університету. Серія Економіка, 2025)
This study was focused on investigating the impact of scenario analysis on the strategic management process of a corporation to enhance its adaptability and competitiveness. The research examined scenario analysis as a key strategic planning tool in conditions of uncertainty. It included a historical review of the development of the scenario approach, particularly its application within corporations. The main stages of scenario analysis were described: identification of key factors, determination of driving forces of change, formulation of alternative scenarios, their evaluation, and the development of strategic responses. The primary approaches to scenario construction were also discussed, including expert judgement methods, analysis of key factors and trends, stress testing, and system dynamics. As a practical case, the activities of the Ukrainian agricultural company Kernel, operating under high uncertainty caused by geopolitical and economic factors, were studied. The scenario analysis conducted outlines three possible development paths for the company over the next 3-5 years: optimistic (restoration of stability and growth), baseline (adaptation to wartime conditions), and pessimistic (crisis and contraction of operations). For each scenario, the impact of external factors was assessed, key financial indicators were forecast, and strategic recommendations were developed. The findings indicated that using scenario analysis helps companies increase the flexibility of managerial decisions, adapt to unstable environments, and reduce strategic risks. The recommendations proposed for Kernel include diversification of logistical routes, enhancement of operational efficiency, active cooperation with international financial institutions, and development of high value-added products. The practical recommendations developed from the Kernel case can be adapted by other agricultural holdings in Ukraine and worldwide to design scenarios in response to economic challenges